Transcriptome analyses of Atlantic salmon (Salmo salar L.) erythrocytes infected with piscine orthoreovirus (PRV). Issue 2 (August 2015) - Dahle, Maria Krudtaa; Wessel, Øystein; Timmerhaus, Gerrit; Nyman, Ingvild Berg; Jørgensen, Sven Martin; Rimstad, Espen; Krasnov, Aleksei
Abstract: Heart and skeletal muscle inflammation (HSMI) is a widespread disease of farmed Atlantic salmon ( Salmo salar L.) and is associated with piscine orthoreovirus (PRV) infection. PRV is detectable in blood long before development of pathology in cardiac- and skeletal muscle appear, and erythrocytes have been identified as important target cells for the virus. The effects of PRV infection on cellular processes of erythrocytes are not known, but haemolytic anemia or systemic lysis of erythrocytes does not seem to occur, even with high virus loads in erythrocytes. In this study, gene expression profiling performed with high-density oligonucleotide microarray showed that PRV infection of erythrocytes induced a large panel of virus responsive genes. These involved interferon-regulated antiviral genes, as well as genes involved in antigen presentation via MHC class I. PRV infection also stimulated negative immune regulators. In contrast, a large number of immune genes expressed prior to infection were down-regulated. Moderate reduction of expression was also found for many genes encoding components of cytoskeleton and myofiber, proteins involved in metabolism, ion exchange, cell–cell interactions as well as growth factors and regulators of differentiation. PRV did not affect expression of genes involved in heme biosynthesis, gas exchange or erythrocyte-specific markers, but some regulators of erythropoiesis showed decreased transcription levels. These results indicate that PRV infection activates innate antiviral immunity in salmon erythrocytes, but suppresses other gene expression programs. Gene expression profiles suggest major phenotypic changes in PRV infected erythrocytes, but the functional consequences remain to be explored. Highlights: PRV infection of erythrocytes induces virus responsive genes. No effect of PRV infection on genes involved in heme biosynthesis or gas exchange. PRV infection induced suppressor of cytokine signalling (SOCS)1 and IL-10 receptor. Moderate reduction of genes involved in metabolism and ion exchange.